2018
DOI: 10.1186/s12864-018-4604-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic, transcriptomic, and proteomic reannotation of human herpesvirus 6

Abstract: BackgroundHuman herpesvirus-6A and -6B (HHV-6) are betaherpesviruses that reach > 90% seroprevalence in the adult population. Unique among human herpesviruses, HHV-6 can integrate into the subtelomeric regions of human chromosomes; when this occurs in germ line cells it causes a condition called inherited chromosomally integrated HHV-6 (iciHHV-6). Only two complete genomes are available for replicating HHV-6B, leading to numerous conflicting annotations and little known about the global genomic diversity of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 62 publications
7
65
0
Order By: Relevance
“…One possible explanation for the abundance of U85‐derived epitopes among the eluted peptides is the relatively high affinity for DRB1*03:01 (IC 50 = 18 nM). Another potential explanation might be a high abundance of the protein in infected cells, but although previous work has demonstrated expression of the U85 gene as an immediate‐early transcript in HHV‐6B‐infected SupT1 cells , the protein product was not detected in a recent proteomic study of cell lysates . The reason for this is not known, but the presence of specific T‐cell responses suggests that expression of the U85 protein and generation of the CD4 T‐cell epitope also occurs during natural infections.…”
Section: Discussionmentioning
confidence: 97%
“…One possible explanation for the abundance of U85‐derived epitopes among the eluted peptides is the relatively high affinity for DRB1*03:01 (IC 50 = 18 nM). Another potential explanation might be a high abundance of the protein in infected cells, but although previous work has demonstrated expression of the U85 gene as an immediate‐early transcript in HHV‐6B‐infected SupT1 cells , the protein product was not detected in a recent proteomic study of cell lysates . The reason for this is not known, but the presence of specific T‐cell responses suggests that expression of the U85 protein and generation of the CD4 T‐cell epitope also occurs during natural infections.…”
Section: Discussionmentioning
confidence: 97%
“…Of note, only seven other published iciHHV‐6B (four US and three Asiatic) strains had a different entire U39 sequence. The phylogenetic analysis showed that the same partial sequence was found in 18 community HHV‐6B strains (of which nine US strains) but was clearly different from those of 74 others including 20 US strains, with one to 10 differences among the 16 single nucleotide polymorphisms highlighted for HHV‐6B (Figure A,B) . This led us to suggest that the DNA detected in the blood corresponded to iciHHV‐6B originated from the liver and unlikely from an endogenous community strain.…”
Section: Resultsmentioning
confidence: 99%
“…The part of U39 sequenced in the transplanted liver and the plasma of the recipient was compared to published sequences of different HHV-6B and iciHHV-6B strains from different countries. 7,14,18,19 Only the different sequences represented by a reference strain were used to build a phylogenetic tree using the Maximum Likelihood Table 1). These results were compatible with the presence of iciHHV-6B in the donor (≥1 copy per cell).…”
Section: Phylogenetic Analysis Of a Part Of U39 Genementioning
confidence: 99%
See 2 more Smart Citations